Correction: Predictors of post-pericardiotomy syndrome after native valve-sparing aortic valve surgery. - Theresa Holst; Lisa Müller; Noureldin Abdelmoteleb; Sina Stock; Tatiana M Sequeira Gross; Evaldas Girdauskas (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0306306.].